Agile approaches for successfully managing and executing projects in the fourth industrial revolution - Bolat, Hur Bersam, 1971-; Temur, Gul Tekin, 1983- (IGI Global, 2019)
"This book examines how various stages of project management discipline will be changed by the effect of Industry 4.0. It covers topics such as the use of big data analytics within vital issues such as project life cycles and project risk management and the utilization of artificial intelligence to improve estimating man-machine-hours-costs and quality of projects"--